Mixed-oxide spinels usable in anticorrosive coating compositions - Kalendová, Andrea (Univerzita Pardubice, 1999)
The compounds having a general formula of AB2O4, containing Mg(II), Ca(II), or Zn(II) as A and Fe(III) or Al(III)as B were prepared and subjected to comparative investigations with respect to their anticorrosive activities as pigments for organic coating. The anticorrosion efficiency data obtained in the course of standard corrosion tests indicate that these nontoxic pigments of a new generation are prospective materials for applications of interest.
Keywords: antikorozní pigmenty; korozní testy; spinelový typ; nátěrové systémy